2020
DOI: 10.30909/vol.03.02.183204
|View full text |Cite
|
Sign up to set email alerts
|

Volcanic ballistic projectile deposition from a continuously erupting volcano: Yasur Volcano, Vanuatu

Abstract: Volcanic Ballistic Projectiles (VBPs) are the main hazard to life and infrastructure from Strombolian eruptions. This eruption style is a tourist drawcard, exposing people to VBP hazard. Most of the research on VBPs to date has been focussed on understanding how they form and their trajectory. However, little focus has been placed on how they are spatially distributed within VBP fields or the inclusion of these data into hazard and risk assessments. In this study, we used a drone to image the east and south fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
(93 reference statements)
0
21
0
Order By: Relevance
“…(2017) and Iezzi et al. (2019) have shown that acoustic directionality from volcanic eruptions are consistent with ballistic directionality at Yasur volcano, Vanuatu (Fitzgerald et al., 2020), which may equate to increased hazard in some azimuths around the volcano.…”
Section: Introductionmentioning
confidence: 83%
“…(2017) and Iezzi et al. (2019) have shown that acoustic directionality from volcanic eruptions are consistent with ballistic directionality at Yasur volcano, Vanuatu (Fitzgerald et al., 2020), which may equate to increased hazard in some azimuths around the volcano.…”
Section: Introductionmentioning
confidence: 83%
“…Vanuatu, located in the Pacific Ring of Fire with six active volcanoes, has attracted volcanologists [11][12][13][14]. Like many rural communities in PICs, most villages located outside the capital city of Port Vila still maintain customs that have been practiced over generations.…”
Section: Introductionmentioning
confidence: 99%
“…During basaltic volcanic eruptions, common types of bombs have included ballistically ejected varieties, including 'breadcrust' bombs, as well as rounded features that form with ballistic ejection, such as accretionary balls (also known as lava balls), that form through addition of mass to their outer portions during rolling within lava ows. Ballistic volcanic bombs have been of particular interest for both understanding volcanic processes to examine their in-ight dynamics 4,5,9 , the mechanisms of magma fragmentation 10 , as well as the dangers that they present for the destruction of manmade structures, and the preservation of life [11][12][13] , and they are a key aspect when considering the growing consensus that lower magnitude eruptions, such as that at La Palma, can cause signi cant local, regional and global damage and potential disasters 14 .…”
Section: Introductionmentioning
confidence: 99%